Practice Deliberation in Collaborative Governance: A Review of Policy for Handling Slums on Riverbanks in the Banjarmasin City (Journal of Pharmaceutical Negative Results, 2023)
This study analyzes and identifies two perspectives that are interrelated, namely the practice of deliberation and collaborative governance. The concept of deliberation in principle requires the achievement of democratic substance in collective decision-making. Meanwhile, collaborative governance is an achievement in finding the best way to implement a policy. This study used a qualitative approach to collect and analyze data. The results of this study explain that the practice of deliberation has not been able to provide a sense of justice for the actors involved in expressing opinions regarding the policy issue of handling slum settlements on riverbanks in Banjarmasin City. This is because the practice of deliberation in collaborative governance is not carried out collectively. Then, collaborative governance in the policy of handling slum settlements on river banks in Banjarmasin City brings together the interests of each actor, which lasts throughout the process of formulating and implementing policies. The practice of deliberation causes opportunities to mutually accommodate each actor's interests to occur more easily. As with collaboration between actors, it is influenced by several phenomena, namely actors having different interests and visions, which causes debates between actors, thereby hindering the deliberation process.